Lima Bean Downy Mildew Epiphytotics Caused by New Physiological Races of Phytophthora phaseoli - Davidson, C R (Plant disease, 2008)
Before 1995, race D of Phytophthora phaseoli, the causal agent of downy mildew on lima bean (Phaseolus lunatus), was the prevalent physiological race in the mid-Atlantic region of the United States. Since 1995, however, new physiological races of P. phaseoli have been responsible for downy mildew outbreaks in previously resistant cultivars in this region. Cultivar differential testing of 180 isolates of P. phaseoli collected between 1994 and 2005 from Delaware and the eastern shore of Maryland has confirmed the presence of two new physiological races. The detection of race E in 1995 and race F only 5 years later in 2000, plus the lack of resistant cultivars to manage the epiphytotics in lima bean, have led to millions of dollars of crop losses. Intra- and interspecific genetic variation of Phytophthora spp. and isolates were assessed using amplified fragment length polymorphism DNA fingerprinting. Primer groups EcoRI+AG and MseI+C distinguished P. phaseoli and P. capsici from P. infestans but did not distinguish among different races of P. phaseoli